Shelley's Republic of Odours: Aesthetic and Political Dimensions of Scent in 'The Sensitive-Plant'. (September 2013) - Boyson, Rowan
Abstract : Shelley's poetry and prose make frequent reference to odour and fragrance, and this essay offers the first extended consideration of the theme since A. C. Bradley's short 1929 essay. It explores the analogy between metre and scent made by Shelley and Hegel, offering a close reading of 'The Sensitive-Plant' focused on its dolnik prosody and its use of synaesthesia. The materialist and scientific connotations of smell are considered with reference to 'My Lost William' and the work of Thomas Reid and Humphry Davy. The essay argues that Shelley's odoriferous language helps us to rethink the place of the senses in critical theory.